Tools and Methods for Citizens’ Involvement in Microplastics Mapping of Ephemeral Wetlands: The Case Study of Lake Gwelup (Perth, Western Australia) - Atkinson, James A (Curtin University, 2024)
The research is deployed as a case study, tracking the development of tools and methods and their use, in the first instance to discover the presence of microplastics in an ephemeral wetland. Plastics in sizes as small as 15µm have been recovered and characterised from sampling points in the benthos of Lake Gwelup, Western Australia. New tools and methods have been developed and existing techniques have been adapted to support their use by citizen scientists.